27. EFFECTIVENESS OF TELEHEALTH INTERVENTION ON GLYCEMIC CONTROL IN PATIENTS WITH TYPE 2 DIABETES MELLITUS AT LIEN CHIEU DISTRICT MEDICAL CENTER, DA NANG CITY IN 2023-2024: A NON-RANDOMIZED CONTROLLED INTERVENTION STUDY (Vietnam Journal of Community Medicine, 2024)
Objectives: Global health is witnessing a rapid growth in the number of type 2 diabetes mellitus (T2DM) patients, and a key factor in the prevention and treatment of T2DM is the patient’s self-management and medication adherence. Telehealth is an innovative instrument to enhance the healthcare service. This study aims to examine the Telehealth's effect on patients with T2DM at Lien Chieu District Medical Center in Da Nang city.Methods: A non-randomized controlled intervention study using telehealth to enhance outpatient treatment management of patients with T2DM was conducted. We used YouMed application as an telehealth application.Results: The telehealth intervention at Lien Chieu District Medical Center in Da Nang city showed significant HbA1c decrease after 3 months and glucose decrease after 6 months, respectively dropping from 6.75% to 6.60% (p = 0.037) and from 8.31% to 7.61% (p < 0.001).Conclusion: Telehealth has been shown to be effective in improving glycemic parameters, suggesting the potential for broader application of this intervention method in the care of type 2 diabetes patients. In addition, the integration of many patient support features promises to increase the effectiveness of telehealth.
Keywords: Telehealth; type 2 diabetes mellitus; glycemic control; Lien Chieu District Medical Center